2018
DOI: 10.1503/jpn.170102
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of emotional action control in anger-prone women with borderline personality disorder

Abstract: The results indicate reduced lateral prefrontal-amygdala communication during emotional action control in anger-prone women with BPD. The findings provide a possible neural mechanism underlying difficulties with controlling emotional impulses in patients with BPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 51 publications
12
46
0
Order By: Relevance
“…In a randomized, double-blind design, participants received either 24 IU of oxytocin or placebo intranasally. We expected a replication of the results by Bertsch et al (8) with more approach behavior to angry faces in BPD in comparison to avoidance behavior. In the oxytocin condition, we expected reduced approach behavior toward potentially threatening angry stimuli in patients with BPD.…”
Section: Introductionmentioning
confidence: 50%
See 1 more Smart Citation
“…In a randomized, double-blind design, participants received either 24 IU of oxytocin or placebo intranasally. We expected a replication of the results by Bertsch et al (8) with more approach behavior to angry faces in BPD in comparison to avoidance behavior. In the oxytocin condition, we expected reduced approach behavior toward potentially threatening angry stimuli in patients with BPD.…”
Section: Introductionmentioning
confidence: 50%
“…Furthermore, faster initial saccades into the eyes-the most threatening part-of angry faces in patients with BPD suggest approach rather than avoidance behavior to interpersonal threat cues (7). In an experimental approach-avoidance task (AAT), anger-prone women with BPD reacted faster in approaching than avoiding angry-potentially threatening-faces than healthy women did (8). In such tasks, appetitive stimuli, such as happy faces, usually trigger approach behavior in healthy participants, while aversive or threatening stimuli, such as angry faces, trigger avoidance (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore not surprising that reduced prefrontal (particularly orbitofrontal and ventrolateral prefrontal) activations are especially reported in those studies in which patients are instructed to use reappraisal in order to regulate their emotional responses to negative emotional stimuli [38, 39], while no differences or even increased prefrontal activations compared to healthy volunteers were found in emotion paradigms without explicit regulation instructions [40, 41]. In a recent study, we found similar prefrontal activations in patients with BPD and healthy volunteers who were required to control and override fast emotional action tendencies of avoiding angry and ap proaching happy faces [42]. However, the functional coupling between the dorsolateral prefrontal cortex and the amygdala was significantly reduced in the patients.…”
Section: Neurobiological Correlatesmentioning
confidence: 99%
“…Thus, T effects on amygdala reactivity might depend on an individual's motivational tendencies toward threat signals. Indeed, as reviewed earlier, aggressive individuals tend to dwell on threat cues, and some evidence suggests that they show an approach bias toward such stimuli (Beaver, Lawrence, Passamonti, & Calder, 2008;Bertsch et al, 2018;.…”
mentioning
confidence: 89%